الطعن في السنة النبوية في العصر الحديث - د.محمد السايح صالح الكوربو (Aljameai, 2025)
المستخلص :يتناول هذا البحث ظاهرة الطعن في السنة النبوية في العصر الحديث بوصفها إحدى الأدوات المؤثرة في الوعي الديني، لما يترتب عليها من تشويش منهجي في مصادر التشريع, وبهدف البحث إلى تحليل جذور هذه الظاهرة ورصد مظاهرها ودوافعها، وبيان أثرها في تشكيل العقل المسلم المعاصر. وأظهرت الدراسة أن الطعن في السنة النبوية ليس جديدًا من حيث الأصل، غيرأن صورَه المعاصرة اتسمت بالاتساع والتأثير؛ نتيجة انتشار المناهج الاستشراقية والعقلانية والقراءات التاريخية للنصوص، فضلاً عن الدور الذي لعبه الإعلام والفضاء الرقمي في تضخيم الشبهات التي أثيرت حوله ، واتضح أن الطعن يدور حول الطعن في السند والمتن، والدلالة من خلال ردّ المعاني بزعم مخالفتها للعقل، والطعن في حجية السنة في التشريع, كما أن دوافع الطعن تتنوع بين فكرية واجتماعية وسياسية ونفسية وثقافية, وأبراز خطورة الطعن على ثوابت الشريعة ، خاصة في تشكيك الأجيال في هذا المصدر وإضعاف مرجعيتة. وخلصت الدراسة إلى ضرورة مواجهة هذه الظاهرة عبر إحياء منهج المحدثين، والتركيز على التعليم الديني, وتطوير المنصات الرقمية العلمية لذلك، وترسيخ الوعي النقدي الشرعي لدى المتلقي.Abstract:This study examines the phenomenon of casting doubt on the Prophetic Sunnah in the modern era, viewing it as one of the influential tools shaping religious consciousness due to the methodological disruption it causes in the sources of Islamic legislation. The research aims to analyze the roots of this phenomenon, trace its manifestations and motives, and clarify its impact on the formation of the contemporary Muslim mind, while proposing scholarly methods to address it.The study shows that skepticism toward the Sunnah is not new in origin; however, its contemporary forms have become broader and more influential as a result of the spread of Orientalist, rationalist, and historicist approaches to the texts, in addition to the role played by the media and digital space in amplifying the doubts raised about it. The analysis reveals that such skepticism revolves around challenging the authenticity of the chain of transmission and the text itself, as well as contesting its meanings under the pretext that they contradict reason, and disputing the legislative authority of the Sunnah.The motives behind this skepticism vary across intellectual, social, political, psychological, and cultural factors. The study highlights the dangers posed by this phenomenon to the fundamentals of Islamic law, especially through instilling doubt in younger generations about this essential source and weakening its authority. It concludes with the necessity of confronting the phenomenon by reviving the methodology of the hadith scholars, strengthening religious education, developing scholarly digital platforms, and cultivating sound critical awareness among recipients.